2020 8th International Winter Conference on Brain-Computer Interface (BCI) 2020
DOI: 10.1109/bci48061.2020.9061644
|View full text |Cite
|
Sign up to set email alerts
|

Decoding Visual Responses based on Deep Neural Networks with Ear-EEG Signals

Abstract: Recently, practical brain-computer interface is actively carried out, especially, in an ambulatory environment. However, the electroencephalography signals are distorted by movement artifacts and electromyography signals in ambulatory condition, which make hard to recognize human intention. In addition, as hardware issues are also challenging, ear-EEG has been developed for practical brain-computer interface and is widely used. However, ear-EEG still contains contaminated signals. In this paper, we proposed ro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
3

Relationship

3
5

Authors

Journals

citations
Cited by 14 publications
(7 citation statements)
references
References 40 publications
0
7
0
Order By: Relevance
“…Also, as we looked for minimal channel for practical/mobility, another factor to consider in these conditions is ambulatory. Works such as Lee and Lee ( 2020 ) have already shown that ML approach is more robust against a number of ambulatory conditions. Dataset also matters, as (Nakanishi et al, 2015 ; Ravi et al, 2020 ) already shown effects of different datasets used on performance evaluation.…”
Section: Discussionmentioning
confidence: 99%
“…Also, as we looked for minimal channel for practical/mobility, another factor to consider in these conditions is ambulatory. Works such as Lee and Lee ( 2020 ) have already shown that ML approach is more robust against a number of ambulatory conditions. Dataset also matters, as (Nakanishi et al, 2015 ; Ravi et al, 2020 ) already shown effects of different datasets used on performance evaluation.…”
Section: Discussionmentioning
confidence: 99%
“…This review discusses such algorithms, which can also apply to other types of EEG systems. One such algorithm proposed by Lee and Lee [132] is a two-stream deep neural network that combines a CNN stream for extracting frequency-domain features and a long-short term memory stream for extracting time-domain features. The extracted features from both streams are then combined to map the classification output.…”
Section: Enhancing Ear-eeg Performance With Machine Learning and Sign...mentioning
confidence: 99%
“…To widely spread practical BCI technology, we should consider the use of EEG in the real world. Several state-of-the-art BCI systems have demonstrated increased system performance using deep learning (Lee and Lee, 2020;Lee et al, 2020d;Mammone et al, 2020;Sun et al, 2020), but generally evaluate the system only in laboratory environments. However, some technical problems with external and internal artifacts have been addressed in real-world environments.…”
Section: Challengementioning
confidence: 99%